Electroanalysis of organic compounds at bismuth electrodes: a short review - Lezi, Nikolitsa; Vyskočil, Vlastimil; Economou, Anastasios; Barek, Jiří (Univerzita Pardubice, 2012)
Over the last twelve years, it has been demonstrated that bismuth electrodes have comparable electroanalytical performance to mercury electrodes in the negative potential range. Since the toxicicty of bismuth is lower than that of mercury, bismuth can serve as an alternative “green” electrode material to mercury. However, the great majority of published work at bismuth–based electrodes is concerned with the determination of trace metals by voltammetric techniques with only few applications dealing with the electroanalysis of organic compounds. This work is a review of the field of electroanalysis of organic species at bismuth electrodes. The review covers the different types of bismuth electrodes used for various classes of target organic species that are electroactive at bismuth electrodes and within the electrochemical detection schemes used in conjunction with bismuth-based electrodes.
Keywords: organic compounds; electroanalysis; bismuth electrodes